Perioperative Complications in Elderly Patients Undergoing Intracranial Surgery—A Prospective Observational Study - Kumar, Shailendra; Ramalingam, Kavinkumar K.; Kumar, Vinay; Pandia, Mihir P.; Dube, Surya K. (Journal of Neuroanaesthesiology and Critical Care, 2025)
Elderly patients undergoing intracranial surgery are at high risk of perioperative complications due to physiological changes, comorbidities, and surgical complexity. This study evaluates the incidence and nature of perioperative complications in this population.A prospective observational study was conducted on 150 elderly patients (≥60 years) undergoing elective or emergency intracranial surgery. Preoperative variables, intraoperative events, and postoperative complications were recorded. Statistical tests, including chi-square and t-test, were applied, with a significance threshold of p < 0.05. Univariate and multivariate analyses were performed to identify predictors of poor outcomes.The median age was 65 years (range: 60–82), with 56.7% male patients. Hypertension (59.3%) was the most common comorbidity, and brain tumors (47.3%) were the most frequent diagnosis. Emergency surgeries comprised 30.7%, and 95.3% received general anesthesia. Intraoperative complications included hemodynamic fluctuations (32%), brain bulge (26.7%), and arrhythmias (10%). Blood loss >1,000 mL occurred in 16.7%, with 29.3% requiring transfusion. Postoperatively, electrolyte abnormalities (49.3%) were most common, followed by neurological (23.3%) and cardiovascular (18.7%) complications. The mean hospital stay was 8.1 ± 7.0 days. In-hospital mortality was 20%. Multivariate analysis identified vascular surgery, poor preoperative Glasgow coma scale (GCS), intraoperative hemodynamic instability, and postoperative cardiovascular and neurological complications as significant predictors of poor outcomes (p < 0.05).Elderly patients undergoing intracranial surgery are at risk of major perioperative complications. Identifying high-risk factors such as vascular pathology, poor GCS, neurological or cardiovascular complications, and hemodynamic instability can aid in optimizing perioperative management and improving outcomes.
Keywords: elderly; intracranial surgery; perioperative complications; neurosurgical outcomes